Sosialisasi Pentingnya Kemampuan Belajar Bahasa Inggris Sejak Dini Kelas VI di SDN 50 Bengkulu Tengah - Elisa Narvelia; Desi Anilia; Ikke Wulan Dari; Danang Krisnanda; Dewi Indriyana; Ramdi Setiawan; Densi Oktavia; Muhammad David Rahmanda; Rifka Korinniza; Vidya Cinta Oktaviani; Rika Andriyani (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
This study addresses the lack of English language education in elementary schools in rural areas of Indonesia, focusing on SDN 50 Bengkulu Tengah. The research aims to evaluate the effectiveness of a one-day socialization program on the importance of early English language learning. The program, designed for sixth-grade students, included interactive presentations, English songs as ice-breakers, and basic conversation practice. Data was collected through participatory observation, questionnaires on basic English skills, and semi-structured interviews with teachers and students. Qualitative analysis revealed a significant increase in students' awareness and interest in learning English, with 80% of participants showing active engagement. The study highlights the potential of short-term interventions in sparking interest in English language learning, even in resource-limited settings. However, it also underscores the need for sustained efforts and integration of English into the curriculum to achieve long-term language proficiency improvements.